1995
DOI: 10.1557/jmr.1995.0362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on Ag particle growth and optical properties in Ag/SiO2 glass composite thin films

Abstract: Small Ag particles were embedded in SiO2 glass thin films by a multi-target sputtering method. The mean diameter of Ag particles in the as-deposited film with 28.0 at. % of Ag was estimated to be 4.4 nm and it was increased to 24.0 nm when the film was heat-treated at 700 °C for 3 h. The diameter was proportional to the cube root of the heat-treatment time, suggesting that the Ag particles grew in the supersaturated solid solution. In the optical absorption spectra of the heat-treated films, the absorption pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 12 publications
3
26
1
Order By: Relevance
“…Thus, the particle growth was considered to take place within the pores of the matrix, which would explain the relatively low activation energy associated with Ag diffusion outside the solid matrix [19]. More in relation to the process taking place for NPs surrounded by a solid host, Tanahashi et al [20] conducted a study on the effects of HT on Ag NP growth for sputtered Ag:SiO 2 nanocomposite films. The authors reported an activation energy in association with Ag particle growth during ripening of 88.1 kJ mol À1 (0.913 eV) [20].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the particle growth was considered to take place within the pores of the matrix, which would explain the relatively low activation energy associated with Ag diffusion outside the solid matrix [19]. More in relation to the process taking place for NPs surrounded by a solid host, Tanahashi et al [20] conducted a study on the effects of HT on Ag NP growth for sputtered Ag:SiO 2 nanocomposite films. The authors reported an activation energy in association with Ag particle growth during ripening of 88.1 kJ mol À1 (0.913 eV) [20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent advances in high-intensity femtosecond (fs) laser pulses have made it possible to fabricate small noble metal particles [9][10][11] such as gold and silver atoms embedded in glasses as well as encode various functional microstructures inside transparent materials [12][13][14]. In particular, such metal nanoparticles embedded in glasses are expected to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 nanoparticles in Ag + -activated phosphate glass without heat treatment was demonstrated for the first time to clarify the origin of a RPL glass dosimeter by highly successive fs laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a variety of modifier oxides were introduced into the glass network by different routs like ion exchange [22,23], ion implantation [24], irradiation-assisted processing, i.e. ion [25], electron [18] and laser [26] irradiation, sol-gel synthesis [27], reducing atmosphere treatment [28] or co-sputtering of metal-glass target [29].…”
Section: Introductionmentioning
confidence: 99%